1991
DOI: 10.1172/jci115436
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human T cell lymphotropic virus type I proviral DNA and its gene expression in synovial cells in chronic inflammatory arthropathy.

Abstract: To investigate the pathogenesis of human T cell lymphotropic virus type I (HTLV-I)-associated chronic inflammatory arthropathy (HAAP), we sought to detect proviral DNA in the articular lesions. For the detection of proviral DNA, we used the polymerase chain reaction (PCR). Proviral DNA was detected not only in the peripheral blood mononuclear cells (PBMCs) and synovial fluid cells (SFCs), but also in the T lymphocyte-depleted cultured synovial cells (CSCs). These findings suggest that the infection by HTLV-I m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(44 citation statements)
references
References 44 publications
(23 reference statements)
1
41
0
2
Order By: Relevance
“…Adherent cells (considered to be synoviocytes and macrophages) and nonadherent cells (considered to be lymphocytes and multinucleated cells) were obtained. Cytoplasmic RNA was extracted from both cells using the standard AGPC method (12) assessed the infiltrating synovial mononuclear cells in the presence of 1.0 pg/ml of phytohemagglutinin (PHA, Sigma) and 10 units/ml of IL-2 (Shionogi, Tokyo). Similarly, synoviocytes obtained from the synovial tissues of 5 of the RA patients were cultured longer than 3 passages (1 1).…”
Section: Methodsmentioning
confidence: 99%
“…Adherent cells (considered to be synoviocytes and macrophages) and nonadherent cells (considered to be lymphocytes and multinucleated cells) were obtained. Cytoplasmic RNA was extracted from both cells using the standard AGPC method (12) assessed the infiltrating synovial mononuclear cells in the presence of 1.0 pg/ml of phytohemagglutinin (PHA, Sigma) and 10 units/ml of IL-2 (Shionogi, Tokyo). Similarly, synoviocytes obtained from the synovial tissues of 5 of the RA patients were cultured longer than 3 passages (1 1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Koyanagi and colleagues [37] demonstrated HTLV-1 tropism for CD8 + T cells, monocytes, and B cells in the majority of the asymptomatic HTLV-1-positive individuals studied, as well as in patients with HTLV-1-related ATL or HAM/TSP. Other groups have also confirmed these observations and have reported that HTLV-1 also infects macrophages [37], DCs [38], synovial fluid cells [39], and astrocytes [40] among others when the target cells are examined in vivo. Perhaps of great importance in the pathogenesis of HTLV-1-associated neurologic disease is the penetration of the virus into the bone marrow compartment with increasing numbers of HTLV-1 DNA + / RNA -progenitor cells detected in patients suffering from HAM/TSP as compared to patients with ATL [41], thus further demonstrating another layer of complexity with respect to target cell identification that likely involves latency, immune invasion, and adaptation to the host.…”
Section: Htlv-1 Infectivity Transmission and Pathogenesismentioning
confidence: 62%
“…Due to the limited amount of genomic DNA from cells in the affected joints, we used PCR to detect HTLV-I proviral DNA. Proviral DNA was detected not only in PBMC and SF mononuclcar cells (SFMC), but also in fresh synovial tissue and cultured adherent synovial stromal cells, but not fresh lymphocytes (19). This finding was the first direct evidence that HTLV-I exhibits tropism to human synoviocytcs composed of macrophages (type A) and fibroblast-like cells (type B), as well as lymphocytes.…”
Section: Pathogenesis Of Htlv-i Arthropathymentioning
confidence: 83%
“…'l'hcse findings allowcd us to spcculate that HTLV-I may potentially induce complex disease spectra which manifest as primary autoimmune disorders. Further investigations from our laboratory revealed that the HTLV-I tax gene (Figure l), known as a transregulatory gene, contributes not only to the induction of synovial cell hyperplasia, but also to the immune response, both in vivo and in vitro (16)(17)(18)(19)(20). The results of thcsc studics strongly suggest that HTLV-I is the etiologic agcnt in HTLV-I-associatcd autoimmune disorders.…”
Section: Introductionmentioning
confidence: 92%